Bosco, the Kodiak bear, on display at Woodland Park Zoological Gardens, n.d. - University of Washington Libraries. Special Collections Division. (1908)
Caption on image: Bosco, the mammoth bear of Kadiack [sic] Island, Alaska. Bear pit, Woodland Park, Seattle. Filed in: Seattle-- To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number